The Impact of Overconfidence Bias on Customer Satisfaction in Digital Banking: A Bivariate Analysis - B. Loganathan, B. Loganathan; P. Sasikumar, P. Sasikumar (Journal of Neonatal Surgery, 2025)
This study investigated the association between overconfidence bias and customer satisfaction in the realm of digital banking. As digital platforms become increasingly prevalent, customers are more reliant on their own financial judgments, which may lead to cognitive distortions such as overconfidence bias. Through a structured survey and quantitative analysis, this study explores whether such bias significantly influences perceived satisfaction with digital banking services. Using statistical tools, such as Pearson correlation, one-way ANOVA, independent samples t-test, and linear regression, 232 participants were analysed. The findings indicated a minimal yet noteworthy relationship between overconfidence and satisfaction, with educational level contributing to variations in overconfidence. This study enhances the understanding of behavioural biases in digital finance and offers implications for improving user engagement and satisfaction through awareness and education.